Coastal fast ice in the Shokalski Strait - V. A. Borodkin; A. P. Makshtas; P. V. Bogorodsky (Лëд и снег)
Field investigations of coastal fast ice near the research station Ice Base on the «Cape Baranova», carried out in 2013–2014, made possible to reveal a number of characteristics of the sea ice cover formation. It has been shown that during winter and early spring the sea ice thickness, being formed due to intensive snow drift and caused by that flooding of the ice cover just near the coast of the Bolshevik Island, substantially grows at its upper boundary, that is typical for the Antarctic seas. At the same time, similar process of the ice growth at a relatively short distance from the coast shows all features characteristic for the ice cover in the Arctic seas, and that is well reproduced by the conceptual numerical sea ice model. Thus, the region of the Ice Base «Cape Baranova» represents a natural laboratory for studying the processes of the sea ice formation in both, the Arctic and Antarctic seas under condition of the same atmospheric forcing. Transformation of the fast ice structure during the summer time is described. Results of the investigations has demonstrated that despite the radical changes in the structure thicknesses of the fast ice remained almost unchanged due to the ice growth on the bottom boundary of the ice cover until a destruction of it in August.